Perceptogram Encoding Weight Reconstructions from THINGSEEG2 - Teng Fei (22496582) (2025)
Perceptogram enables the visualization of presumptive electrode preference and EEG patterns, revealing interpretable EEG feature maps that correspond to distinct visual attributes, such as semantic class, texture, and hue.